2022
DOI: 10.3389/fmicb.2022.846208
|View full text |Cite
|
Sign up to set email alerts
|

Aspen Leaves as a “Chemical Landscape” for Fungal Endophyte Diversity—Effects of Nitrogen Addition

Abstract: Abiotic and biotic factors may shape the mycobiome communities in plants directly but also indirectly by modifying the quality of host plants as a substrate. We hypothesized that nitrogen fertilization (N) would determine the quality of aspen (Populus tremula) leaves as a substrate for the endophytic fungi, and that by subjecting the plants to N, we could manipulate the concentrations of positive (nutritious) and negative (antifungal) chemicals in leaves, thus changing the internal “chemical landscape” for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 73 publications
(98 reference statements)
1
8
0
Order By: Relevance
“…Tables 1 , 2 ; Figures 2 , 4 ). The findings agree with culture-based experimental evidence from Sweden recently (Witzell et al, 2022 ) that N input did not alter the total richness and Shannon diversity of FEFs in 12 aspen genotypes. We suggest that in the alpine meadow ecosystems, total fungal communities harbored in diverse groups of plants tend to persist under increasing N deposition.…”
Section: Discussionsupporting
confidence: 92%
“…Tables 1 , 2 ; Figures 2 , 4 ). The findings agree with culture-based experimental evidence from Sweden recently (Witzell et al, 2022 ) that N input did not alter the total richness and Shannon diversity of FEFs in 12 aspen genotypes. We suggest that in the alpine meadow ecosystems, total fungal communities harbored in diverse groups of plants tend to persist under increasing N deposition.…”
Section: Discussionsupporting
confidence: 92%
“…Endophytes infect the plants from the surrounding environment (Gomes et al, 2018) and the dominance of certain fungi in the culturable fraction may thus re ect the high frequency of these fungi in the environmental inoculum in the region of the study area. The fact that the same morphotypes dominated in the samples from the greenhouse-grown I. balsamina supports this view -in greenhouses, the environmental inoculum is limited to spores that are most abundant in the incoming air (Witzell et al, 2022).…”
Section: Discussionmentioning
confidence: 54%
“…The high colonization rate of Melampyrum and Veronica species indicates that they were suitable substratum for endophytic fungi. The quality of leaves as a habitat for endophytic fungi could not be analysed in this study, but it has been suggested that especially the secondary metabolites, such as potentially antifungal phenolics could be a factor directing the microbiome composition (Witzell et al, 2022). In previous studies, some of these compounds have been found to be high in rust-resistant alternate host species (Kaitera & Witzell, 2016;Piispanen et al, 2023).…”
Section: Discussionmentioning
confidence: 96%
“…Fungal communities in tree foliage are not uniformly distributed or stationary ( Toju et al., 2019 ); their composition is influenced by several factors including host genotype ( Albrectsen et al., 2010b ), growth site ( Siddique et al., 2021 ), seasonal factors ( Albrectsen et al., 2010b ), ontogeny ( Bourassa et al., 2005 ; Boutigny et al., 2013a ), tissue type ( Siddique et al., 2021 ), and host-associated consumers ( Arnold et al., 2003 ; Albrectsen et al., 2010b ; Siddique et al., 2021 ). The mechanisms underpinning these relationships are not fully understood but it has been suggested that both the host’s chemical defense responses ( Ullah et al., 2017 ; Witzell et al., 2022 ) and competition between members of the mycobiome may help shape the microbial community ( Wemheuer et al., 2019 ; Siddique et al., 2021 ). In the present study, we also obtained results suggesting the occurrence of a transition in the composition of the fungal community.…”
Section: Discussionmentioning
confidence: 99%